Disciplinary Literacy and Responsible Reading: Approaching Indigenous Texts - Wolstein, Ashley; Rackley, Eric (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2025)
While many scholars note the important role disciplinary literacy can play in advancing social justice, much of the current research focuses on how English experts approach canonical texts of Western origin. This article investigates the meaning-making approaches employed by 11 English disciplinarians when approaching texts of Indigenous origin. These scholars participated in semi-structured interviews and participated in a read-aloud. Findings highlight that, in addition to traditional disciplinary practices such as contextualizing, performing definitional work, and drawing upon background knowledge, approaching Indigenous texts requires specific meaning-making practices grounded in Indigenous frameworks and drawing upon specific Indigenous Literary tools. This study hopes to show how disciplinary meaning-making practices, as applied to Indigenous literature, can allow expanded access to these diverse perspectives.